Supply and demand for telecommunication infrastructure - Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The interplay of infrastructure supply and demand is of central interest in line with Web 2.0. As the role of customers turns from a service users' role to an information providers' role, the traffic on existing lines increases and, simultaneously, customers' demand for high-quality infrastructure. On the other hand, infrastructure providers carry investment risks but can hardly internalize the value provided for service providers. In consequence, politicians have to think about how to initiate adequate investment incentives. Using a two-equation estimation approach, a direct competition effect (more service competition increases the supply of infrastructure) can be disentangled from an indirect effect (more service competition increases the demand for infrastructure quality and, as a consequence, increases the supply of infrastructure). While the direct investment effect is only partially confirmed, the analysis provides evidence for an indirect investment effect for both fix and mobile infrastructure investments. Taking into account cross effects between fix line infrastructure markets and mobile phone infrastructure markets even broadens the view: While the indirect own-market competition effect is still found, the estimation results confirm the idea of asymmetric substitutability between telecommunication infrastructures.
Keywords: K23; L13; L43; L96; 330; telecommunications; infrastructure supply and demand; Telekommunikationsinfrastruktur; Infrastrukturinvestition; Wettbewerb; Telekommunikation; Service Provider; Web 2.0; Medienverhalten; Schätzung; EU-Staaten